Recent Progress on Multifunctional Electrolyte Additives for High‐Energy‐Density Li Batteries – A Review - Dr. Yue Lei; Kaifeng Wang; Dr. Sen Jiang; Dr. Xin Xu; Junzi Zheng; Dr. Junying Yin; Prof. Yunfang Gao (ChemElectroChem)
Abstract The improvement of the safety, specific energy, cycle life and the cost reduction of Li‐ion batteries are hot research topics. Now, in the pursuit of high energy density, the employed high‐energy‐density cathode/anode materials and the increased operation voltage challenge the prevalent electrolyte formula, like the existing ester and ether electrolytes cannot withstand the high‐voltage operation and high‐capacity anode such as lithium (Li), silicon (Si) and silicon‐graphite (Si−C) composite anode. It is recognized that stable electrolyte‐electrode interfaces can avoid the electrolytes side reactions and protect the electrode materials. Up to now, various additives have been developed to modify the electrode‐electrolyte interfaces, such as famous 4‐fluoroethylene carbonate, vinylene carbonate and lithium nitrate, and the LIBs and lithium metal batteries (LMBs) performances have been improved greatly. However, the lifespan of the higher‐energy‐density batteries with Li/Si/Si−C anode and high‐nickel layer oxides cathode materials cannot meet the request due to the lack of ideal electrolyte formula. In this review, we present a comprehensive and in‐depth overview on the electrolyte additives, especially focused on multifunctional additives, the reaction mechanisms of various additives and fundamental design. Finally, novel insights, promising directions and potential solutions for the multifunctional electrolyte additives are proposed to motivate high‐energy‐density Li battery chemistries.